Evaluation of Electrofishing Catch per Unit Effort for Indexing Fish Abundance in Florida Lakes. Issue 1 (27th December 2012) - Hangsleben, Matt A.; Allen, Micheal S.; Gwinn, Daniel C.
Abstract: Electrofishing CPUE data are commonly used to index temporal trends in abundance in fish monitoring programs, but the reliability of this index requires the assumption that the fraction of fish stock caught per unit effort (catchability, q ) is relatively precise and constant through time. We evaluated how fish species, season, and lake affected electrofishing catchability in Florida lakes using a field study. We used the field study results to simulate how variable electrofishing q affects statistical power and type I error rate (i.e., the probability of detecting a difference when in fact no difference occurred). Model selection showed that electrofishing catchability varied by species, season, and lake, and submodels showed that catchability varied by lake for Largemouth Bass Micropterus salmoides and by season for Lake Chubsucker Erimyzon sucetta, and was constant across season and lake for Bluegill Lepomis macrochirus . Our results revealed that statistical power decreased and the type I error rate increased substantially if q varied through time as we observed for Largemouth Bass and Lake Chubsucker. Type I error rates were well above the expected value of 0.05, reaching as high as 0.7 for Largemouth Bass and 0.55 for Lake Chubsucker at high sample sizes. This resulted because increasing sample size improves the ability to detect real changes, but also increases the probability of detecting spurious changes due to variable q (i.e., type I error). Thus, variable catchability hinders our ability to use CPUE data to index trends in fish abundance, and monitoring programs should consider how q varies before relying on CPUE data to index fish abundance.